Full‐field deformation measurements during seismic loading of masonry buildings. Issue 4 (4th July 2016) - Rajaram, S.; Vanniamparambil, P. A.; Khan, F.; Bolhassani, M.; Koutras, A.; Bartoli, I.; Moon, F.; Hamid, A.; Benson Shing, P.; Tyson, J.; Kontsos, A.
Summary: This article demonstrates the potential of the digital image correlation (DIC) method to provide accurate full‐field deformation measurements and successfully monitor the development of damage during seismic excitation of a partially grouted reinforced masonry building. The building was subjected to a sequence of earthquake ground motion records using the Large High Performance Outdoor Shake Table at the University of California, San Diego. The DIC setup was capable of measuring surface deformations of the single‐story building with high frame rate cameras located at a distance greater than 50 ft away. The accuracy of the measurements was assessed with data obtained using mounted displacement transducers. The full‐field deformation data collected by the DIC system was capable to detect strain localization patterns associated with the onset of wall cracking before it could be shown by the displacement sensor data or by post mortem visual inspection. The research findings reported herein demonstrate, for the first time to the authors' best knowledge, the potential of in situ monitoring of actual structures for damage induced by non‐stationary loading profiles using optical metrology. Copyright © 2016 John Wiley & Sons, Ltd.